Metode Guru dalam Pembinaan Nilai-Nilai Akhlak Siswa melalui Shalat Zuhur Berjamaah di SMP Negeri 1 Kecamatan Jujuhan Ilir Kabupaten Bungo - Dian Anggraini Dzulfiana; Mustafa (YASIN, 2026)
The cultivation of students’ moral values through the implementation of congregational Dhuhr prayers at school continues to face various challenges, including low student discipline, suboptimal teacher guidance methods, inconsistent supervision, and the influence of the environment and technological developments. This study aimed to analyze the methods used by teachers to cultivate moral values through congregational Dhuhr prayers, identify the moral values instilled, and examine the supporting and inhibiting factors in their implementation at SMP Negeri 1 Jujuhan Ilir Subdistrict, Bungo Regency. The study employed a qualitative approach with a descriptive design. The research informants consisted of Islamic Religious Education teachers, the school principal, and students. Data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data display, and conclusion drawing. Data trustworthiness was established using source and method triangulation. The results showed that teachers applied the methods of habituation, role modeling, advice, rewards, punishment, supervision, and evaluation in cultivating students’ moral character. The moral values instilled included discipline, responsibility, religiosity, politeness, and social concern. The implementation of moral development was supported by the roles of teachers and families and the availability of school facilities and infrastructure, whereas the inhibiting factors included low student awareness, suboptimal supervision, limited facilities, environmental influences, and technological developments. These findings confirm that moral development through congregational Dhuhr prayers has been implemented effectively but requires consistency in applying the methods and synergy among the school, teachers, families, and the surrounding environment. This study contributes to the development of research on character education based on religious habituation and provides practical implications for schools in strengthening teacher supervision and collaboration with parents to optimize students’ moral development.